Regulation of the PML tumor suppressor in drug-induced senescence of human normal and cancer cells by JAK/STAT-mediated signaling - Hubackova, Sona; Novakova, Zora; Krejcikova, Katerina; Kosar, Martin; Dobrovolna, Jana; Duskova, Pavlina; Hanzlikova, Hana; Vancurova, Marketa; Barath, Peter; Bartek, Jiri; Hodny, Zdenek (Cell cycle (Georgetown, Tex.), 2010)
The Promyelocytic leukemia protein (PML) tumor suppressor is upregulated in several forms of cellular senescence, however the mechanism of its induction is elusive. Here we show that genotoxic drugs that induce senescence, such as 5-bromo-2'deoxyuridine (BrdU), thymidine (TMD), distamycin A (DMA), aphidicolin (APH), etoposide (ET) and camptothecin (CPT) all evoke expansion of PML nuclear compartment and its association with persistent DNA lesions in several human cancer cell lines and normal diploid fibroblasts. This phenomenon was accompanied by elevation of PML transcripts after treatment with BrdU, TMD, DMA and CPT. Chemical inhibition of all JAK kinases and RNAi-mediated knock-down of JAK1 suppressed PML expression, implicating JAK/STAT-mediated signaling in regulation of the PML gene. As PML protein stability remained unchanged after drug treatment, decreased protein turnover was unlikely to explain the senescence-associated increased abundance of PML. Furthermore, binding activity of Interferon Stimulated Response Element (ISRE) within the PML gene promoter, and suppression of reporter gene activity after deletion of ISRE from the PML promoter region suggested that drug-induced PML transcription is controlled via transcription factors interacting with this element. Collectively, our data show that upregulation of the PML tumor suppressor in cellular senescence triggered by diverse drugs including clinically used anti-cancer chemotherapeutics relies on stimulation of PML transcription by JAK/STAT-mediated signaling, possibly evoked by the autocrine/paracrine activities of senescence-associated cytokines.
Keywords: nádorový supresorový protein p53; Gene Expression Regulation, Leukemic; messenger RNA; jaderné proteiny; buněčné jádro; nádorové buněčné linie; signální transdukce; DNA Damage; Promyelocytic Leukemia Protein; Nuclear Proteins; STAT Transcription Factors; Janus kinasa 1; poškození DNA; Signal Transduction; kompartmentace buňky; Janus Kinase 1; Cellular Senescence; Tumor Suppressor Protein p53; Cell Line, Tumor; Transcription Factors; Antineoplastic Agents; Transcription, Genetic; genetická transkripce; Neoplasms; transkripční faktory; Cell Nucleus; responzivní elementy; nádorové supresorové proteiny; protinádorové látky; RNA, Messenger; Humans; nádory; Tumor Suppressor Proteins; transkripční faktory STAT; Response Elements; Cell Compartmentation; protein promyelocytické leukemie; regulace genové exprese u leukemie; lidé; stárnutí buněk